Isolation and Preliminary Characterization of Bacteriophages for Bdellovibrio bacteriovorus - Althauser, Mary (1972)
Ten bacteriophages that attack and lyse saprophytic strains of Bdellovibrio bacteriovorus were isolated. Morphological, serological, and host-range studies revealed that there were four different bdellovibrio phages present among the isolates. One of the phages lysed a strain of B. bacteriovorus that requires the presence of a suitable bacterial host for growth. The phage attached to the bdellovibrio cells in the absence of the bacterial host cells; lysis occurred only in the presence of host cells. The 19 saprophytic bdellovibrio strains employed in the phage host-range studies were grouped on the basis of their susceptibility to phage lysis.